Heteropoly Acid-Based Catalysts for Hydrolytic Depolymerization of Cellulosic Biomass - Luo, Xiaoxiang; Wu, Hongguo; Li, Chuanhui; Li, Zhengyi; Li, Hu; Zhang, Heng; Li, Yan; Su, Yaqiong; Yang, Song (Frontiers in Chemistry, 2020)
Cellulose is the most abundant source of biomass, which can be converted into monosaccharide or other chemical platform molecules for the sustainable production of chemicals and fuels. Acid catalysts can promote hydrolytic degradation of cellulose into valuable platform molecules, which is of great significance in the development of chemicals and biofuels. However, there are still some shortcomings and limitations of the catalysts for the hydrolytic degradation of cellulosic biomass. Heteropoly acid (HPA), as a green catalyst, seems to be more conducive to the degradation of cellulosic biomass due to its extreme acidity. HPAs can be designed in homogeneous and heterogeneous systems. Moreover, they can be easily separated from the products in both systems by a simple extraction process. According to the unique properties of HPAs (e.g., good solubility, high thermal stability, and strong acidity), using heteropoly acid-based catalysts to depolymerize and convert cellulose into value-added chemicals and biofuels has become one of the most remarkable processes in chemistry for sustainability. In this review, the characteristics, advantages, and applications of HPAs in different categories for cellulose degradation, especially hydrolysis hydrolytic degradation, are summarized. Moreover, the mechanisms of HPAs catalysts in the effective degradation of cellulosic biomass are discussed. This review provides more avenues for the development of renewed and robust HPAs for cellulose degradation in the future.